Synthesis of Perylene-Tagged Internal and External Electron Donors for Magnesium Dichloride Supported Ziegler–Natta Catalysts - Guzeev, Bogdan A.; Mladentsev, Dmitry Y.; Sharikov, Mikhail I.; Goryunov, Georgy P.; Uborsky, Dmitry V.; Voskoboynikov, Alexander Z. (Synthesis, 2019)
We report on the synthesis of three perylene-tagged electron donors representing three major types – phthalates, diethers, and alkoxysilanes – which are of importance for the subsequent studies of MgCl2-supported Ziegler–Natta catalysts by means of laser scanning confocal fluorescence microscopy. The obtained products were unambiguously characterized, including by X-ray crystal structure analysis; their photophysical properties (absorption and emission spectra) were investigated as well. Additionally, a reliable and convenient protocol for the multigram synthesis of the required starting material – 3-bromoperylene (PerBr) – was developed. The key step of this method was synthesis of trialkylsilyl-substituted perylenes, which were further separated by means of flash chromatography followed by conversion of the isolated 3-trialkylsilyl-substituted product to PerBr.
Keywords: 3-substituted perylenes; electron donors; Ziegler–Natta catalysts; emission spectra; fluorescence spectra